Perceiving online public opinion : a study of the effects of Facebook opinion cues, opinion climate congruency, & source credibility on willingness to speak out - Leong, Alisius Deon Xue Li (2019)
Facebook’s novel affordances and unique features have transformed the way people assess public opinion. Opinion cues such as user-generated comments (UGCs) and aggregated user representations (AURs) offer users original ways to infer public opinion. Drawing on the spiral of silence theory, a nascent body of literature has investigated the roles of UGCs and AURs on perceptions of the opinion climate. However, the inconclusive findings and the recent launch of reaction emojis highlight a need to re-examine the role of AURs, and the relative influence of UGCs and AURs on perceptions of the opinion climate. Innovative features on Facebook have also triggered new research trajectories to understand how heuristic cues such as source credibility might influence the public’s willingness to speak out. This experimental study (embedded in the form of an online survey) adopted a 3 x 2 x 2 between-subjects factorial design. This study provided 360 Facebook users aged 21 and above with a mock-up Facebook page, manipulated in terms of opinion cues (UGCs-only vs. AURs-only vs. UGCs-and-AURs), opinion climate congruency (congruent opinion climate vs. incongruent opinion climate), and source credibility (high source credibility vs. low source credibility). Theoretically, this study contributes to the spiral of silence literature as it is the pioneering piece to elucidate how AURs represented by reaction emojis influence perceptions of the opinion climate. It is also the first study to investigate how source credibility may influence silencing effects. Practically, the findings can inform relevant stakeholders about the dynamics of online public opinion formation to help them identify and inhibit subversive online behavior. It also illuminates the role of source credibility that can inform the engenderment of effective communication and outreach efforts.